2D-DIGE-Based Proteomic Profiling with Validations Identifies Vimentin as a Secretory Biomarker Useful for Early Detection and Poor Prognosis in Oral Cancers. (22nd April 2022) - Sivagnanam, Ananthi; Shyamsundar, Vidyarani; Kesavan, Pallavi; Krishnamurthy, Arvind; Thangaraj, Soundara Viveka; Venugopal, Divyambika Catakapatri; Kasirajan, Hemashree; Ramani, Pratibha; Sarma, Vinutha Rachapudi; Ramshankar, Vijayalakshmi
Abstract : Oral tongue squamous cell carcinoma (OTSCC) is an aggressive cancer with high morbidity and mortality rates, despite multimodality management. There are currently no clinically relevant molecular markers that identify patients at higher risk of recurrence and failure. We undertook 2D-DIGE proteomic profiling to study the differentially expressed proteins in OTSCC evaluating their role in prognosis. 2D-DIGE coupled with tandem mass spectrometry was performed on tissues obtained from early staged OTSCC along with its paired apparently adjacent normal tissue samples (n = 10 ). Top upregulated protein was validated using immunohistochemistry (n = 345 ), comprising of retrospective early stage OTSCC (n = 150 ) and prospective series of oral precancers, normal, and oral cancers (n = 195 ). Saliva samples collected from oral cancer and precancer samples were analyzed by ELISA (n = 146 ). We found statistically significant differential expression in 151 proteins out of 700 proteins quantified. Top ten differentially regulated proteins were identified using mass spectrometry analysis. We found vimentin, the mesenchymal protein, to be the most upregulated protein in tongue tumor tissues compared to adjacent apparent normal tissues. Vimentin was found to be significantly overexpressed in oral precancers along with cancers compared to normal tissues. The vimentin expression correlated significantly with differentiated states of oral precancers and cancers. Vimentin was also detected at significantly higher levels in saliva collected from oral precancer and cancer patients compared to normal healthy volunteers. Validation of vimentin in an independent series of retrospective early staged OTSCC showed that the vimentin expression is significantly associated with treatment failures and poorer DFS. The vimentin expression is useful as both poor prognostic and early detection marker in oral cancer. Vimentin detection in saliva can be a diagnostic test to detect oral precancers that may have malignant potential, needing closer follow-up, and disease monitoring.